2022
DOI: 10.1002/pc.26605
|View full text |Cite
|
Sign up to set email alerts
|

Toughening and rapid self‐healing for carbon fiber/epoxy composites based on electrospinning thermoplastic polyamide nanofiber

Abstract: This article fabricated toughening and self-healing carbon/epoxy composites based on electrospinning thermoplastic polyamide nanofiber (PAnf). When the incorporation of PAnf was merely 1.2 wt%, the interlaminar shear and bending strength of composites increased by 17.6% and 14.7%. The two main toughening mechanisms were the entangled porous nanofiber structure with a large specific surface area and the strong interface resulting from the interaction between PAnf and epoxy. Multiple short beam shear cycles gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…components at a molecular level, which results in a homogeneous phase system. 76,77 The variations observed in the diameter distribution (Figure S9) and the average diameter of nanofiber mats attributed to the changes in the chemical structure, electrical conductivity, and the spinning solution viscosity as a result of BPPTA incorporation at different concentrations. The tendency of composite structures with strong inter-chain hydrogen bridges between the polymer components to form larger structures may have part in the increase of the fiber diameters with BPPTA reinforcement up to 3% concentration.…”
Section: Morphological Analysis Of the Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…components at a molecular level, which results in a homogeneous phase system. 76,77 The variations observed in the diameter distribution (Figure S9) and the average diameter of nanofiber mats attributed to the changes in the chemical structure, electrical conductivity, and the spinning solution viscosity as a result of BPPTA incorporation at different concentrations. The tendency of composite structures with strong inter-chain hydrogen bridges between the polymer components to form larger structures may have part in the increase of the fiber diameters with BPPTA reinforcement up to 3% concentration.…”
Section: Morphological Analysis Of the Cnmsmentioning
confidence: 99%
“…The strong intermolecular interactions between the matrix and the additive polymer molecules result in improved mechanical and thermal properties due to the effective load transfer as well as the enhanced interfacial adhesion and connectivity of the resulting network. 40,76,78 However, after an optimal filling ratio, over-fusion of the nanofibers may have negative effects on the tensile and flexural properties. 85 While the increase in mechanical performance is expected to continue due to the decrease in average fiber diameter and increase in inter-chain interactions as the additive ratio increases, it is observed that the mechanical properties decrease with additive loading higher than an optimal filling ratio, which is 3%, 5%, and 1% for tensile strength, toughness, and elastic modulus, respectively.…”
Section: Mechanical Properties Of the Cnmsmentioning
confidence: 99%
“…However, even core‐shell nanofibers also degrade the composite's mechanical properties, which usually has not been taken into account 18,19 . Accommodating healing agent with nanofibers can avoid flaws caused by Microcapsules and hollow microfibers, but it may weaken interfacial bonding between fibers and matrix, which reduces stress transfer ability between the interface 20–22 . Modified core‐shell nanofibers have potential to achieve good self‐healing properties of the composite while enhancing their strength.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that when the thickness of the nanofibers was 35 μm, the material absorbed impact energy more effectively and exhibits higher residual strength and less impact damage. Chen et al [ 26 ] prepared thermoplastic polyamide nanofibers by electrostatic spinning technique and carbon fiber composites containing PA nanofibers, and the experimental results showed that the interlaminar shear strength and flexural strength of the composites increased by 17.6% and 14.7%, respectively, when the introduction of PA nanofibers was 1.2 wt%. All the above studies showed that the introduction of nanofibers not only did not reduce the original mechanical properties, but also improved the impact resistance or other mechanical properties of the material to some extent.…”
Section: Introductionmentioning
confidence: 99%